O processo de gest??o dos cursos de pedagogia a dist??ncia no Distrito Federal - Pereira, Ana Cristina Rodrigues (2017)
Statistics show that online Education (EaD) in Brazil has a real tendency to grow, with undergraduate and postgraduate courses being offered and supported by regulatory frameworks of higher education, by specific milestones of the online Education and by laws and decrees of the Ministry of Education Education (MEC). The courses offered in this modality aim to promote a facilitating study through printed material, audio, video (recorded or live), content broadcasted via satellite or by digital technologies, mediated by computer, tablets and cell phones, in response to the great demand of people who need the flexibility that the modality provides and also promoting the democratization of access to higher education. That being said, today online education has more visibility and acceptance by society and the undergraduate courses are the ones that have the largest number of enrollments and the Pedagogy course is in the first place. The present work consists of the analysis of the management process of online Pedagogy courses that offer initial training in the institutions of higher education of the Federal District and the possible relations with the CPC reached by them and with the objectives of: a) Mapping the institutions of Higher education in the Federal District that offer online Education courses and identify the courses that are best evaluated in the CPC; B) Identify the process of management of distance education courses in the Institutional Development Plan (IDPs) and PPCs (Pedagogical Project of the Courses) of the selected institutions; C) to carry out a case study among educational institutions that offer online Pedagogy courses in order to identify similarities and differences in the management process of Pedagogy courses in the Federal District. We chose a qualitative approach of exploratory nature as a documental analysis method. Documentation research (PDI and PPC) and semi-structured interviews (coordinators of the courses) were chosen as instruments of data generation, and content analysis was carried out in all cases. From the research, differences were observed in the legal nature of the institutions and in the course offer model, but direct relationship hasn??t been found between these differences and the results achieved by Higher Education Institute (HEI) according to the CPC of each one. The differences observed were: operation of the course with tutors in the public and private HEI, number of students enrolled, number of poles, number of hours, length of courses, governance model with some similarities as grouping of courses by schools / institutes / colleges etc. among other issues. The similarities discovered were on the provision of common subjects, the reformulation of the IDP and PPC, and the requirements of managing a distance licentiate course in the face of market uncertainties and governmental public policies